The Effect of Health Fatalism and Health-Seeking Behaviors on the Frequency of Non-Medication Coping Strategy Use in Women with Urinary Incontinence in Turkiye - Basgol, Sukran; Kucukkaya, Burcu (Springer London Ltd, 2025)
Introduction and Hypothesis Health-seeking behavior is habitual among people in a society, resulting from the interaction and balance between health needs, health resources, and socioeconomic factors. This study seeks to investigate the influence of health fatalism and health-seeking behaviors on the frequency of non-medication coping strategy use among women with urinary incontinence in Turkiye. Methods This cross-sectional study was conducted between 8 August 2024, and 22 September 2024. A total of 354 women voluntarily participated in the study, which was disseminated via social media platforms and online forums. Data collection involved the use of a Personal Information Form, the Health Fatalism Scale (HFS), the Health-Seeking Behaviour Scale (HSBS), and the Non-Medication Coping Strategies for Urinary Incontinence Frequency of Use Scale (NMCS-UIFUS). Results The mean total HFS score was 50.39 +/- 29.70, the mean total HSBS score was 38.76 +/- 20.48, and the mean NMCS-UIFUS score was 35.69 +/- 17.31. A statistically significant, strong negative correlation was found between health fatalism and health-seeking behavior, whereas a significant, strong positive correlation was observed between health fatalism and the frequency of non-medication coping strategy use for urinary incontinence (p < 0.001). Regression analysis revealed that health fatalism explained 37% of the variance in the frequency of non-medication coping strategy use for urinary incontinence, whereas health-seeking behavior accounted for 30% of the variance (p < 0.001). Conclusions Our study demonstrated that women with urinary incontinence exhibit moderate levels of health fatalism, health-seeking behaviors, and the frequency of non-medication coping strategy use; further, as health fatalism increases, health-seeking behavior decreases, whereas the frequency of non-medication coping strategy use rises.
Keywords: Frequency Of Non-Medication Coping Strategy Use; Health Fatalism; Health-Seeking Behavior; Urinary Incontinence; Women